Evaluation of Hematological Factors and Micronutrients Among Children Infected with Enterobius vermicularis - Akram, Haneen Esam; Al-Warid, Harith Saeed (Iraqi Journal of Science, 2023)
Malnutrition, anemia, and micronutrient deficits may be associated with Enterobius vermicularis infection. Hence, the subject has recently received a lot of attention. The goal of this study was to analyse the nutritional, hematological and micronutrient status of children infected with E. vermicularis. This research was carried out in Baghdad from October 2021 to the end of March 2022. The study comprised 100 children of both sexes, ranging in age from 3-16 years. All individuals nutritional status was assessed using the weight-for-age Z score and the height-for-age Z score. As well as cellophane tape samples and blood samples were collected from all individuals. The cellophane tape samples were examined under microscope for E. vermicularis detection. Whereas blood samples were processed to assess many factors which were: haemoglobin, ferritin, total binding capacity (TIBC), serum iron, serum zinc and serum magnesium. Results revealed significant correlations between E. vermicularis infection occurrence and each of age and gender, even though most infections were noticed among females and among those who were between 3-9 years. The results also showed that the nutritional status, based on weight for age Z score, was significantly (P˂0.05) related to E. vermicularis occurence. Moreover haemoglobin, ferritin, serum iron, serum zinc and serum magnesium were noted to have significantly (P˂0.05) decreased among those who were E. vermicularis positive compared with E. vermicularis negative group. While total iron-binding capacity (TIBC) increased significantly among E. vermicularis positive children. The current investigation revealed that E. vermicularis infection had significant implications on several haematological elements, as well as stunting nutritional shortages. As a result, a lower prevalence of intestinal parasite infection (particularly enterobiasis) among children would almost certainly benefit their growth, development and educational outcomes.